Analysis of Constitutional Court Decision No.56/PUU-XVII/2019 on Electoral System and Legislative Candidacy Requirements - Tania Sahda; Ahmad Ahmad; Ayu Sipah; William Ramadhan; Sumartono Sumartono (Universitas Muhammadiyah Tangerang, 2023)
The Constitutional Court Decision Number 56/PUU-XVII/2019 represents an important turning point in strengthening Indonesia’s electoral democratic system, particularly regarding the eligibility of former convicts to run for regional head elections. Concerns over the limited nature of Article 7 paragraph (2) letter g of Law Number 10 of 2016 are highlighted, as this provision allows former convicts, including those convicted of corruption, to nominate themselves for regional head positions merely after public disclosure, without any mandatory waiting period. This article examines the constitutional foundations used by the Constitutional Court in formulating a conditionally constitutional norm, including the imposition of a mandatory waiting period and substantive disclosure of legal status. The Court emphasizes that disclosure alone is insufficient to guarantee the integrity of public office candidates, and that a waiting period constitutes an essential requirement. Furthermore, this article analyzes the systemic implications of the decision, including the strengthening of ethical standards for candidates, improvement of the quality of public information during elections, enhancement of legal certainty for election organizers and participants, and the Court’s role as a guardian of public morality. The findings indicate that stricter regulation of former convicts contributes significantly to safeguarding democratic integrity and preventing the normalization of political corruption.